LECTURERS’ PERCEPTIONS IN FOSTERING ENTREPRENEURIAL ACTIVITIES AT UNIKL: THE CHALLENGES - Ngah, Suhaiza; Ramlan, Rosnizza (PEOPLE: International Journal of Social Sciences, 2015)
Entrepreneurship is said as a key driver of economic growth and development. The need to produce more graduates with entrepreneurial mindset from higher learning institutions is becoming vital. To ensure that this happens, it is critical for the institutions to have a correct infrastructure is in place to facilitate the developing of entrepreneurship culture. As an engineering technology university, fostering entrepreneurship culture at University Kuala Lumpur (UNIKL) is a challenge and it is especially hard to change these students’ mindsets and attitudes towards entrepreneurship. This paper aims to present and discuss the challenges in fostering the entrepreneurship culture, in the forms of entrepreneurial activities, particularly at UNIKL from entrepreneurship lecturers’ perceptions. Data are gathered through observations and interviews. The results of the study showed that there challenges faced by lecturers and university in their mission in implementing entrepreneurial activities. Among the issues are financial aids, students’ participation and interest in entrepreneurial activities, and support system. The findings of the study would be useful for the university to enhance and improve the current approach in embedding entrepreneurship culture in the university.